Identifikasi Kesulitan Siswa Pondok Pada Pembelajaran Konvensional Dalam Menyelesaikan Soal Sistem Persamaan Linear Satu Variabel - Rofiki, Ahmad; Panglipur, Indah Rahayu; Murtinasari, frida (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study was conducted to identify the types of difficulties experienced by students in solving PLSV problems. Descriptive type of research using test instruments and interview guidelines. The research location at MTs ar Riyadh Jenggawah Jember in class VII a total of 30 students. Subjects with the identification results of post-test results had difficulty with operations, concepts, and understanding the problem as many as 3 people. The indicators in the study include three parts, namely difficulties in operations, difficulties in concepts, and difficulties in understanding the problem. From the results of the data obtained, 41.5% of students had difficulty operating, 65% had difficulty in mathematical concepts, and 50% had difficulty in understanding the problem. Based on the results of the analysis obtained, the subject has difficulty in determining the result of an operation through the process of subtraction, addition, multiplication, and division (difficulty in operations), the subject has difficulty in classifying and using the appropriate theorems and formulas (difficulty in concepts), and the subject has difficulty in visualizing / describing / rewriting the contents of the problem in the form of a mathematical model (difficulty understanding). The factors that cause difficulties experienced by students are not only from within students but also from teaching staff who only stick to conventional methods and rarely use learning media so that in teaching and learning activities students are less active.